2016
DOI: 10.1016/j.fluid.2016.07.026
|View full text |Cite
|
Sign up to set email alerts
|

A consistency test for α-functions of cubic equations of state

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
103
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 134 publications
(106 citation statements)
references
References 41 publications
3
103
0
Order By: Relevance
“…Development of the translated-consistent tc-PR and tc-RK cubic equations of state for a safe and accurate prediction of pure-compound densities and other thermodynamic properties -4 -by Le Guennec et al [1] also tested whether 12 α-functions, generally available in process simulation software programs, were or not able to pass the proposed consistency test. They concluded that eight over twelve of these well-known α-functions (Soave 1972 [5], Soave 1984 [6], Gibbons-Laughton [7], Stryjek-Vera [8], Boston-Mathias [9], Mathias-Copeman [10], Mathias [11], Twu 1995 [12,13]) failed the proposed consistency test whatever the values of the parameters are.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 4 more Smart Citations
“…Development of the translated-consistent tc-PR and tc-RK cubic equations of state for a safe and accurate prediction of pure-compound densities and other thermodynamic properties -4 -by Le Guennec et al [1] also tested whether 12 α-functions, generally available in process simulation software programs, were or not able to pass the proposed consistency test. They concluded that eight over twelve of these well-known α-functions (Soave 1972 [5], Soave 1984 [6], Gibbons-Laughton [7], Stryjek-Vera [8], Boston-Mathias [9], Mathias-Copeman [10], Mathias [11], Twu 1995 [12,13]) failed the proposed consistency test whatever the values of the parameters are.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…(4). As explained by Le Guennec et al [1], the set of (L, M, N) parameters can be labeled consistent if the resulting α-function satisfies the constraints defined by Eq. (3).…”
Section: Estimation Of Consistent Twu91 α-Function Parametersmentioning
confidence: 99%
See 3 more Smart Citations